1991
DOI: 10.1007/bf03347116
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glucose ingestion and fasting on plasma immunoreactive beta-endorphin, adrenocorticotropic hormone and Cortisol in obese subjects

Abstract: It has been demonstrated that opioid peptides are involved in the stimulation of food intake in rats and that the circulating beta-endorphin levels are increased in genetically obese rodents. Therefore, to assess whether the changes in food intake may influence circulating beta-endorphin levels in obese subjects, plasma beta-endorphin, ACTH and cortisol concentrations were determined in obese patients after an oral glucose load and during a 7-day total starvation. Baseline plasma beta-endorphin concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In our study, fasting ␤-endorphin levels under basal conditions as well as total ␤-endorphin response during OGTT in obese patients were higher than in normal-weight subjects in accordance with previous reports [16 -18]. Other studies, however, have been unable to demonstrate significant changes in ␤-endorphin levels following either oral glucose [31] or a high-carbohydrate mixed meal load [19]. The known stimulatory effect of ␤-endorphin on insulin secretion [12,13] and the increased responsiveness of pancreatic ␤-cells to ␤-endorphin in obesity [14,15] may contribute at least in part to the hyperinsulinemia and enhanced insulin response seen in our obese patients.…”
Section: Figsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, fasting ␤-endorphin levels under basal conditions as well as total ␤-endorphin response during OGTT in obese patients were higher than in normal-weight subjects in accordance with previous reports [16 -18]. Other studies, however, have been unable to demonstrate significant changes in ␤-endorphin levels following either oral glucose [31] or a high-carbohydrate mixed meal load [19]. The known stimulatory effect of ␤-endorphin on insulin secretion [12,13] and the increased responsiveness of pancreatic ␤-cells to ␤-endorphin in obesity [14,15] may contribute at least in part to the hyperinsulinemia and enhanced insulin response seen in our obese patients.…”
Section: Figsupporting
confidence: 91%
“…Results from previous studies on the influence of weight loss on ␤-endorphin levels have been contradictory, with no response after substantial weight loss [20], a 7-day fast [31], or diet-induced weight loss [18,19,34]. Scavo et al [35] have reported a significant reduction in ␤-endorphin levels following substantial weight loss achieved by caloric restriction and physical exercise and suggested decreased food intake as the cause of reduced ␤-endorphin levels.…”
Section: Figmentioning
confidence: 95%
“…Plasma Bendorphin concentrations were not affected by a 7-day total fast nor by refeeding (4). Weight loss of 18% did not alter basal endorphin levels in obese subjects (133).…”
Section: Endogenous Opioidsmentioning
confidence: 74%
“…3 No. 4 July 1995 377 impact of changes in cortisol level on insulin m e t a b lism and other effects such as blood pressure, lipid levels, adipocyte growth in obese individuals remains speculative at present.…”
Section: Perspectivementioning
confidence: 99%
“…These include nonnutritional sucking [22] and instillation of glucose or other sweet liquids on the tongue [23,24]; glucose is supposed to provide analgesia by stimulating incretion of ß-endorphins [23,[25][26][27]] by a preabsorptive mechanism [28]. However, there have been few studies on nonpharmacological analgesia in the premature, and the methods used have reduced, but not abolished the signs of pain perception [29][30][31][32][33][34].…”
Section: A 16mentioning
confidence: 99%